Afatinib plus vinorelbine versus trastuzumab plus vinorelbine in patients with HER2-overexpressing metastatic breast cancer who had progressed on one previous trastuzumab treatment (LUX-Breast 1): an open-label, randomised, phase 3 trial. Issue 3 (March 2016) - Harbeck, Nadia; Huang, Chiun-Sheng; Hurvitz, Sara; Yeh, Dah-Cherng; Shao, Zhimin; Im, Seock-Ah; Jung, Kyung Hae; Shen, Kunwei; Ro, Jungsil; Jassem, Jacek; Zhang, Qingyuan; Im, Young-Hyuck; et al.
Summary: Background: Trastuzumab resistance is a key therapeutic challenge in metastatic breast cancer. We postulated that broader inhibition of ErbB receptors with afatinib would improve clinical outcomes compared with HER2 inhibition alone in patients who had progressed on previous trastuzumab treatment. LUX-Breast 1 compared afatinib plus vinorelbine with trastuzumab plus vinorelbine for such patients with HER2-positive metastatic breast cancer. Methods: We did this open-label trial at 350 hospitals in 41 countries worldwide. We enrolled female patients with HER2-overexpressing metastatic breast cancer who had progressed on or following adjuvant trastuzumab or first-line treatment of metastatic disease with trastuzumab. Participants were randomly assigned (2:1) to receive oral afatinib (40 mg/day) plus intravenous vinorelbine (25 mg/m 2 per week) or intravenous trastuzumab (2 mg/kg per week after 4 mg/kg loading dose) plus vinorelbine. Randomisation was done centrally and stratified by previous trastuzumab treatment (adjuvant vs first-line treatment), hormone receptor status (oestrogen receptor and progesterone receptor positive vs others), and region. The primary endpoint was progression-free survival, assessed in the intention-to-treat population. This trial is closed to enrolment and is registered with ClinicalTrials.gov, NCT01125566 . Findings: Between Aug 26, 2010, and April 26, 2013, we enrolled 508 patients: 339 assigned to the afatinib group and 169 assigned to the trastuzumab group. Recruitment was stopped on April 26, 2013, after a benefit–risk assessment by the independent data monitoring committee was unfavourable for the afatinib group. Patients on afatinib plus vinorelbine had to switch to trastuzumab plus vinorelbine, afatinib monotherapy, vinorelbine monotherapy, or receive treatment outside of the trial. Median follow-up was 9·3 months (IQR 3·7–16·0). Median progression-free survival was 5·5 months (95% CI 5·4–5·6) in the afatinib group and 5·6 months (5·3–7·3) in the trastuzumab group (hazard ratio 1·10 95% CI 0·86–1·41; p=0·43). The most common drug-related adverse events of grade 3 or higher were neutropenia (190 [56%] of 337 patients in the afatinib group vs 102 [60%] of 169 patients in the trastuzumab group), leucopenia (64 [19%] vs 34 [20%]), and diarrhoea (60 [18%] vs none). Interpretation: Trastuzumab-based therapy remains the treatment of choice for patients with HER2-positive metastatic breast cancer who had progressed on trastuzumab. Funding: Boehringer Ingelheim.